Relationship Between Food Consumption Patterns and Nutritional Status in Nambo Sub-District Community - Aisyah Az-Zahrah Mansur; Nina Indriyani Nasruddin; Amiruddin Eso (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Nutritional status is an individual's health condition, which is determined by the degree of physical need for energy and nutrients obtained from food. The most important behavior that can affect nutritional status is consumption pattern. This is because the quantity and quality of consumed food and drink will affect nutritional intake, which in turn it will affect the health of individuals and society. Purposes: The purpose of this study is to determine the relationship between consumption patterns of carbohydrate source foods and nutritional status in the people of Nambo District. Method: This research is an observational analytic study with a cross sectional approach. This study's population includes all residents of the Nambo District. The research sample consisted of 106 respondents, who were selected using the purposive sampling technique. Data collection included examining nutritional status by weighing and measuring height as well as conducting interviews using Food Recall 24 Hours for 2 days. Data were analyzed by Spearman's rank test. Results: The results of this study indicate that there is a significant relationship (p < 0.05) between the consumption patterns of carbohydrate source foods and nutritional status in the people of Nambo District, and the value of r = 0.493 indicates the strength of the correlation between consumption patterns of carbohydrate source foods and nutritional status in the people of Nambo District is moderate in nature with a positive correlation direction, which indicates a unidirectional correlation direction. Conclusion: There is a relationship between consumption patterns of carbohydrate source foods and nutritional status among the people of Nambo District.